The Issue of Artistic Image of Nature and Method In The Works Of Isajan Sultan (On The Example Of “The Missing Motherland”) - Davronova Shohsanam G'aybulloevna (Universitas Muhammadiyah Sidoarjo, 2022)
The article describes the views of the writer Isajon Sultan on the art of creating an artistic image, his methodological research on the example of the story